A qualitative study of support for young people who self-harm in residential care in Glasgow - Judith Piggot; Charlotte Williams; Stephen McLeod; Joanne Barton (Scottish Journal of Residential Child Care)
A recent study found that 39 per cent of young people in residential care in Scotland had self-harmed compared to 18 per cent of young people living with their birth parents and 14 per cent of young people in foster care (Meltzer, Lader, Corbin, Goodman & Ford, 2004). Another study of young people with experience of residential care in Glasgow found that almost half of respondents had self-harmed or injured themselves at some point in their lives and that the self-harm had predominantly occurred while the young people were living in residential care. Indeed, this study in Glasgow found that one-third of 13-17 years olds in residential care had self-harmed and that 10 per cent of young people in residential care used self-harm as a coping strategy when distressed compared to less than 1 per cent of young people in the general population (Scottish Health Feedback, 2001). These studies suggest that despite the belief that young people's needs can be better met in residential care settings, young people in residential care actually constitute a high-risk population for self harm (Robinson, Auckland, Crawford & Nevison, 1999). Studies to date in residential care settings suggest that elevated levels of emotional and behavioural disturbance continues and it remains unclear if the experience of residential care addresses the needs of young people who self-harm (Vostanis, 2000).